Jogos Baseados em Localização para Narrativas Transmedia - António Emanuel Silva da Costa Moura (2015)
This paper results from a study through the association of location-based games and its game mechanics as potential forces in contexts of transmedia storytelling. There are several location-based games in the current market, in some cases, also related to transmedia storytelling. Applying these games in the tourism and transmedia contexts make the experience even more attractive and interactive while collecting information on those locations. The study of location-based games and its game mechanics in transmedia storytelling contexts is essential to understand what the best solutions for a location-based game in a transmedia context for tourism, applying it successfully on projects with larger dimensions. Understanding the theoretical foundations that underpin the basis of various game design guidelines, as well as the variety of game mechanics by which one can choose in accordance with the characteristics of each project help to figure out the best solutions for games based projects in location. After this study we developed a game based on location, situated within the FEUP campus - Lost in FEUP. Despite representing a small location, the framework developed is intended to be easily scalable to a location-based game for transmedia storytelling with the dimensions of a city. Then, we implemented a working prototype of a location-based game to guide the new students of FEUP and was also created a transmedia narrative. The tests and inquiries about the prototype implemented meant that several aspects were improved, above all, making the game even more intuitive. The results also showed that the main objectives were successfully met, considering the creation of a location-based game in a transmedia context, with scalable geo-referenced mechanics for projects with larger dimensions. This prototype was tested from the beginning to the end by some participants who approved this experience based on location and also confirmed the usefulness of other platforms of transmedia storytelling in gathering information about these locations. Thus, the necessary guarantees have been achieved, so that in future can be applied the knowledge of the research and the developed framework in location-based projects with the same characteristics but with higher scales.